Maternal Mortality Rate at East Ogan Komering Ulu (East OKU) Regional Public Hospital Over a Four Year Period: Trends, Its Associated Factors and Neonatal Outcome - Kesty, Cindy; Saputra, Hendra S (Indonesian Socety of Obstetrics and Gynecology, 2019)
Objective: To determine the MMR trends, its associated factors, and neonatal outcome at East OKU Regional Public Hospital from 2013 until 2016. Methods: This descriptive study was performed from January 2013 until December 2016 in maternity ward and Intensive Care Unit (ICU) of East OKU Regional Public Hospital, South Sumatera. Data was collected from medical records. There were 17 maternal deaths, but 1 data was excluded due to lack of data. Results: We recorded 2,191 pregnancies and 17 maternal deaths. Over 4 years, the lowest MMR occurred in 2013 (229/100,000) and achieved its peak in 2014 (1,306/100,000). Then, MMR followed downward trend dropping from 1,087/100,000 in 2015 until 588/100,000 in 2016. Most of deceased were childbearing age women (50.0%), multigravida (62.5%), but nulliparous (50.0%), and aterm (87.5%). The major etiology of maternal deaths were hypertensive disorder (37.5%), followed by hypertensive disorder + hemorrhage and hypertensive disorder + infection in the same proportion. MMR were higher in inborn cases (87.5%), born via C-section (87.5%), and treated for less than 48 hours (93.75%). Alive neonatal were born in most cases (62.5%). Conclusion: MMR trends in our hospital were fluctuating with a downward trend, but still much higher than the MDGs target in 2015 (102/100,000). Hypertensive disorder plays significant role in maternal deaths. In addition, most of neonates were born alive. We hope that this study can be a feedback for hospital to do maternal and perinatal audit. Keywords: Factors, Maternal mortality rate, Neonatal outcome, Regional public hospital, Trends     Tujuan: Untuk menentukan pola, faktor yang berkaitan, dan luaran neonatus di RSUD OKU Timur dari 2013 hingga 2016. Metode: Studi deskriptif dilakukan dari Januari 2013 hingga Desember 2016 di bangsal kebidanan dan unit perawatan intensif RSUD OKU Timur, Sumatera Selatan. Data dikumpulkan dari rekam medik. Terdapat 17 kematian ibu, tetapi 1 data dieksklusi karena data yang kurang lengkap. Hasil: Terdapat 2.191 kehamilan, dan 17 kematian ibu. Selama 4 tahun, AKI terendah terjadi pada 2013 (229/100.000) dan mencapai puncaknya pada 2014 (1.306/100.000). Kemudian, AKI mengalami penurunan dari 1.087/100.000 pada 2015 hingga 588/100.000 pada 2016. Mayoritas sampel berusia reproduktif (50,0%), multigravida (62,5%) dan nulipara (50,0%), serta aterm (87,5%). Mayoritas kematian ibu disebabkan oleh hipertensi dalam kehamilan (HDK) (37,5%), diikuti oleh HDK + perdarahan dan HDK + infeksi dalam jumlah yang sama. AKI lebih tinggi pada ibu yang melahirkan di RS (87,5%), melahirkan melalui sectio caesaria (87,5%), dan dirawat selama kurang dari 48 jam (93,75%). Mayoritas neonatus dilahirkan hidup (62,5%). Kesimpulan: Pola AKI di RSUD berfluktuasi dengan pola menurun, tetapi masih jauh lebih tinggi dari target MDGs pada tahun 2015 (102/100,000). Hipertensi dalam kehamilan berperan signifikan terhadap kematian ibu. Mayoritas neonatus dilahirkan hidup. Studi ini diharapkan dapat menjadi masukan bagi rumah sakit untuk melakukan audit maternal dan perinatal. Kata kunci: Angka kematian ibu, Faktor, Luaran neonatus, Pola, Rumah sakit umum daerah